Encapsulated cobalt-porphyrin as a catalyst for size-selective radical-type cyclopropanation reactions - Otte, Matthias; Kuijpers, Petrus F.; Tröppner, Oliver; Ivanovic-Burmazovic, Ivana; Reek, Joost N.H.; de Bruin, Bas (Chemistry - A European Journal, 2014)
A cobalt-porphyrin catalyst encapsulated in a cubic ML cage allows cyclopropanation reactions in aqueous media. The caged-catalyst shows enhanced activities in acetone/water as compared to pure acetone. Interestingly, the ML encapsulated catalyst reveals size-selectivity. Smaller substrates more easily penetrate through the pores of the "molecular ship-in-a-bottle catalysts" and are hence converted faster than bigger substrates. In addition, N-tosylhydrazone sodium salts are easy to handle reagents for cyclopropanation reactions under these conditions. © 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.